2020
DOI: 10.5935/1518-0557.20190084
|View full text |Cite
|
Sign up to set email alerts
|

Blastocysts derived from 0PN oocytes: Genetic and clinical results

Abstract: Objective:To analyze the genetic and clinical outcomes of blastocysts derived from 0PN oocytes after IVF/ ICSI.Methods: This retrospective observational study included patients aged 40 years or younger submitted to IVF/ICSI with their own oocytes and with blastocysts derived from 0PN oocytes between January 2015 and April 2018. The clinical outcomes of 0PN blastocyst transfers were analyzed. Genetic tests were performed on biopsied 0PN blastocysts with Next Generation Sequencing.Results: A total of 27 0PN blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…However, Li et al (2015) reported that 0PN blastocysts had similar clinical outcomes to 2PN blastocysts and advised culturing 0PN embryos to the blastocyst stage for selection. Consistent with these findings, recent studies have shown that blastocyst culture of 0PN embryos can result in notable clinical pregnancies and live births [ 5 , 7 9 ]. The quality and implantation potential of blastocysts can be predicted by the morphological parameters of cleavage-stage embryos, including the day 3 blastomere number, fragmentation and symmetry [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, Li et al (2015) reported that 0PN blastocysts had similar clinical outcomes to 2PN blastocysts and advised culturing 0PN embryos to the blastocyst stage for selection. Consistent with these findings, recent studies have shown that blastocyst culture of 0PN embryos can result in notable clinical pregnancies and live births [ 5 , 7 9 ]. The quality and implantation potential of blastocysts can be predicted by the morphological parameters of cleavage-stage embryos, including the day 3 blastomere number, fragmentation and symmetry [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 61%
“…Generally, embryos derived from 0PN zygotes are not recommended for clinical use [ 1 ]. However, several studies have reported that these seemingly abnormal embryos can result in successful pregnancies and live birth after transfer, which has raised the value of 0PN embryos, especially for patients without two pronuclei (2PN) embryos [ 2 – 9 ]. Consequently, revealing the clinical value of 0PN embryos is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies of the genetic characteristics of 0PN and 1PN embryos have suggested that a considerable number of 0PN and 1PN embryos may have a normal chromosomal composition, and thus may be considered for transfer when no embryos developing from 2PN zygotes are available [8][9][10]. Previous studies have reported that 0PN and 1PN cleavage stage embryos resulted in a lower implantation rate (IR) and live birth rate (LBR) when compared with 2PN cleavage stage embryos [11][12], while the IR and LBR were comparable between 0PN-and 1PN-derived blastocyst transfers and those of 2PN-derived blastocyst transfers [12][13]. However, some research suggested that 0PN-and 1PN-derived blastocyst transfers resulted in a lower IR and LBR than 2PN-derived blastocysts, especially in ICSI cycles [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason for 0PN-derived embryos is thought to be due to PN being overlooked in the microscopic assessment at a fixed time point 1 . Some 0PN-derived embryos develop into morphologically normal blastocysts, and there are reports of healthy babies being born from their transfer [1][2][3][4][5][6][7][8][9][10] . However, transfer of the 0PN-derived embryo is not recommended as per the European Society of Human Reproduction and Embryology (ESHRE) guidelines; thus, most of them are discarded without being transferred 11 .…”
mentioning
confidence: 99%